ANALISIS KONSUMSI ENERGI BUS LISTRIK TRAYEK YOGYAKARTA-SURAKARTA - , YUSUF ARIFIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The mobility of modern society requires a supporting component which is capable to meet transportation commmunity activities. Transportation sector, which still relies on fossil fuels also contributes to CO2 pollution that resulting to greenhouse effect. Based on these conditions, this study designed an energy consumption analysis of the electric bus in Yogyakarta-Surakarta route in hopes of becoming the initial idea in the development of mass transportation that is more energy efficient and environmentally friendly in Indonesia. In this study, measurement of driving cycle in Yogyakarta-Surakarta route is performed by using Garmin GPS 76SCX to obtain further parameters for calculation of electric bus energy consumption. Results of electric bus energy consumption calculation will be compared to the ICE bus energy consumption calculation in order to know which type of bus requires less energy. Results of driving cycle masurement in Yogyakarta-Surakarta route was a graph of driving cycles and kinematic parameters such as 135,35 km mileage, 14845 s travel time, 32 km/h average speed, and a maximum speed on 94,93 km/hours. Energy consumption calculation is done by dynamic modeling through driving cycle data to obtain the total energy consumption of bus. The result energy consumption of electric bus was 2,702 to 3,209 KWh / km and the energy consumption of ICE bus was 4,850 kWh / km. These results indicate that the electric buses require less energy than the ICE bus. Keywords: electric bus, ICE bus, driving cycle, energy